Estrategia metodológica innovadora para el desarrollo del pensamiento lógico Matemático - Pallasco Llano, Karina Elizabeth (2021)
Teacher is involved in the development of learning through the appropriate application of methodological strategies, therefore, it is neccesary innovating the development of their pedagogy. In this sense, the goal of this study is propossing an innovative methodological strategy for the developing of mathematical logical thinking with students of sixth elementary level in "Ana Páez" Elementary School. The qualitative investigation were the methodology applied to analyze the teaching and learning process through the observing to the sixth elementary level’s teacher in mathematics area. Moreover, the inductive and analytical method were used to consider the elements and the functioning of the educational action. For this reason, the proposal was the development of a didactic guide, which includes an innovative strategy based on problem solving, resources and technological media for six contents in each chapter of the school text in the developing of mathematical logical thinking. This investigation will contribute that teachers encourage their students the learning in mathematics area according their needs, also includes the launching for students community in the Basic Education career. As the final result, this didactic guide will enable the interest and attention by the students.